Research on the impact effect of multimodal transport on domestic and international dual circulation: Evidence from China's railway and water transport. - Liu Wei; Zheng Xueli; Li Yunhan; Li Xia; Liu Li (PLoS ONE)
As an important part of the modern integrated transportation system, multimodal transport can promote changes in the transportation structure and serve as a crucial lever for upgrading the logistics industry and promoting domestic and international economic and trade development. Based on panel data from 31 provinces in China from 2017 to 2023, a fixed-effects model was constructed to empirically test the mechanism and impact of multimodal transport on domestic and international dual circulation. The findings reveal that the development of multimodal transport has a positive effect on both domestic and international circulations, with a more significant impact on the latter. Specifically, waterway multimodal transport significantly promotes both circulations, while railway multimodal transport only significantly affects the domestic circulation. Furthermore, the impact of multimodal transport on domestic and international dual circulations exhibits notable regional heterogeneity, with multimodal transport in eastern regions having a stronger effect on international circulations and that in central regions having a stronger effect on domestic circulations. This paper analyzes the theory of the multimodal transport's impact on domestic and international dual circulation, provides a practical basis and reference for further research on the development of multimodal transport in relation to domestic and international dual circulation.